Chest CT in the post-COVID era - Maria A. Karnaushkina; Anastasia D. Strutynskaya; Gulzhagan E. Alichubanova (LLC "MEDIAFORMAT", 2022)
Chest CT is one of the leading methods for diagnosing lung diseases. During the COVID-19 pandemic, it has become an indispensable research method for the diagnosis, excluding alternative diseases, and dynamic observation. The acute course of COVID-19 varies in severity, ranging from asymptomatic infection to fulminant respiratory failure. CT is one of the methods for diagnosing the severity and predicting the course of a new coronavirus infection. Radiological symptoms in patients recovered from COVID-19 may persist with or without changes or even progress to various severity. There can be 3 different reasons of these changes: Persistence of CT symptoms after COVID-19, The appearance of new symptoms after COVID-19 and Diseases that are "masks"post-COVID-19. This article depicts the role of chest CT in managing a patient with persistent, progressive, or newly detected CT changes in the lung tissue after COVID-19, which are often misinterpreted as post-COVID syndrome.